(untitled) (Raparin Journal of Humanities (RJH), 2026)
The significance of “place” emerges as one of the most vital elements of the novel, serving as the setting where events unfold and through which characters move. At times, place acts as the central axis of the narrative work. In the realm of the novel—and specifically in this work—place is often deeply intertwined with questions of self, identity, and existence. Place in a novel differs from its reality in the physical world; it is a fusion of fact and imagination, possessing its own unique characteristics and distinct dimensions. The importance of place lies in its role as an active element in the development and structure of the story, as well as in shaping the nature of characters and their relationships. It is a space that encompasses and influences the entire narrative framework. We can assert that a creative novelist is one who bestows creative value upon a place, utilizing it to activate other narrative elements such as characters, time, and storytelling techniques. Kurdish novelists have devoted immense attention to “place,” treating it as a fundamental pillar in their works. This stems from the fact that the essence of the Kurdish struggle for survival is rooted in the land. Land and place are primary catalysts in the Kurdish quest to achieve an independent identity and exercise the right to self-determination. Essentially, the struggle is a struggle for the land, because land signifies identity (as exemplified in Ibrahim Ahmed’s novel Zhani Gal). Accordingly, we have chosen to study the concept of place in the novel Bahar-i Rash (The Black Spring) by the distinguished writer Ahmed Mohammed Ismail. In this novel, the author addresses the Anfal genocide committed against the Kurdish people by the former Ba’athist regime in the 1980s. Through the narrative, he highlights the attempts to obliterate Kurdish identity by depopulating the land of Kurdistan of its indigenous inhabitants through mass murder and forced displacement. However, Kurdish resilience proved stronger than the enemy’s brutal and aggressive methods. This eternal bond of love between the land of Kurdistan and its people is a central theme of the novel. Based on this premise, the research topic was selected: “Manifestations of Place in the Novel Bahar-i Rash.” The study explores the concept of place through two main sections.